SERS of Rhodamine 6G on substrates with laterally ordered and random gold nanoislands - Yukhymchuk, V.O.; Kostyukevych, S.A.; Dzhagan, V.M.; Milekhin, A.G.; Rodyakina, E.E.; Yanchuk, I.B.; Shepeliavy, P.Ye.; Valakh, M.Ya.; Kostyukevych, K.V.; Lysiuk, V.O.; Tverdokhlib, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Preparation and study of laterally ordered and disordered arrays of Au nanoislands as SERS substrates are reported. Developed technology allows obtaining SERS substrates with long-term stability (up to six months), efficient (up to 10⁴) and laterally homogenous enhancement of the Raman signal from molecular analyte. The substrates developed are suitable for Raman bio-diagnostics, because their plasmon resonance can be tuned within the range 700-900 nm that falls into the transparency window of human tissues. The dependence of optical and enhancement properties of the substrates on their morphology has been studied. The morphology of the Au island film and their plasmon resonance spectrum depend noticeably on the nominal Au thickness and post-annealing temperature, while the duration of annealing is of minor importance. Formation of nanoholes in the case of Au substrates on holographically pre-patterned polymer film opens up the possibility of additional Raman enhancement via the "hot spot"-effect.